Utilization of Speech Events in the Marunjuk Custom of the Batak Toba Ethnic Group as a Medium for Learning Cultural Values in Multicultural Education - Asriaty R Purba; Zacklyn Dwi Vanesa Imanuela Lumban Gaol; Flansius Tampubolon; Warisman Sinaga; Ramlan Damanik (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to analyze speech events in the Marunjuk tradition of the Toba Batak ethnic group and evaluate its potential as a source of learning cultural values ??in the context of multicultural education. The Marunjuk tradition is a form of traditional wedding ceremony that is full of meaning and social symbols, which is carried out by the Toba Batak community by involving various elements of oral communication. This study employs a qualitative approach, incorporating observation, documentation, and discourse analysis techniques, grounded in the theory of speech events developed by Dell Hymes (Speaking). The results of the study indicate that there are ten main stages in the Marunjuk tradition containing 57 speech event data, which include values ??such as respect, gratitude, togetherness, and social responsibility. The ten stages are: entering the party hall, delivering tudu-tudu sipanganon, delivering dengke simudur-udur, manjalo tumpak, mambagi jambar, marsiseanan, handing over panandaion, handing over tintin marangkup, mangulosi, tingkir tangga/paulak une (ulaon sad). From an educational perspective, this speech event serves as a concrete representation of cultural practices that can be utilized in local wisdom-based learning, particularly in strengthening the Pancasila student profile and developing character through language and cultural education. This research suggests integrating the Marunjuk custom as a contextual teaching resource in primary and secondary education curricula.